Inducing indel mutation in the SOX6 gene by zinc finger nuclease for gamma reactivation: An approach towards gene therapy of beta thalassemia. Issue 3 (30th November 2017) - Modares Sadeghi, Mehran; Shariati, Laleh; Hejazi, Zahra; Shahbazi, Mansoureh; Tabatabaiefar, Mohammad Amin; Khanahmad, Hossein
Abstract: β‐thalassemia is a common autosomal recessive disorder characterized by a deficiency in the synthesis of β‐chains. Evidences show that increased HbF levels improve the symptoms in patients with β‐thalassemia or sickle cell anemia. In this study, ZFN technology was applied to induce a mutation in the binding domain region of SOX6 to reactivate γ‐globin expression. The sequences coding for ZFP arrays were designed and sub cloned in TDH plus as a transfer vector. The ZFN expression was confirmed using Western blot analysis. In the next step, using the site‐directed mutagenesis strategy through the overlap PCR, a missense mutation (D64V) was induced in the catalytic domain of the integrase gene in the packaging plasmid and verified using DNA sequencing. Then, the integrase minus lentivirus containing ZFN cassette was packaged. Transduction of K562 cells with this virus was performed. Mutation detection assay was performed. The indel percentage of the cells transducted with lenti virus containing ZFN was 31%. After 5 days of erythroid differentiation with 15 μg/mL cisplatin, the levels of γ‐globin mRNA were sixfold in the cells treated with ZFN compared to untreated cells. In the meantime, the measurement of HbF expression levels was carried out using hemoglobin electrophoresis and showed the same results. Integrase minus lentivirus can provide a useful tool for efficient transient gene expression and helps avoid disadvantages of gene targeting using the native virus. The ZFN strategy applied here to induce indel on SOX6 gene in adult erythroid progenitors may provide a method to activate fetal hemoglobin expression in individuals with β‐thalassemia. Abstract : Using the ZFN technology, indel in SOX6 gene was induced. The gamma globin gene was overexpressed. We were able to increase the amount of HbF by manipulating the SOX6 gene.